Education for rural people. The role of education, training and capacity development in poverty reduction and food security (Food and Agriculture Organization of the United Nations RomeIT, 2009)
Seeks to assist policy makers dealing with rural poverty, food insecurity and education challenges confronting rural people. It also seeks to address the correlation between education, training, empowerment and food security, mainly through a number of examples from all over the world. It is also about strengthening the capacity of rural people to achieve food security.
Keywords: FAO